Reimagining 2D to 3D: Towards a Seamless AI-Augmented Workflow for High-Fidelity Animation Production - Zainal, Izani; Mustaffa, Fauzan; Razak, Aishah (Journal of Ecohumanism, 2025)
AI-powered tools for content generation are rapidly gaining prominence in the digital media landscape. A significant challenge lies in transforming AI-generated 2D images into high-quality 3D animations. This research proposes a novel workflow combining advanced AI functionalities with traditional animation methods. Key limitations addressed include tool compatibility, achieving photorealism, overcoming AI creative constraints, and enhancing workflow efficiency. Our solution integrates AI tools like ChatGPT and Midjourney with 3D software (Blender), facilitating a smooth transition from concept to final product. Stable Diffusion is leveraged to enhance 3D animation realism. Creators maintain artistic control through manual interventions. By optimizing the process from scripting to editing, we aim to revolutionize 3D animation production, particularly for AI-to-3D conversions. This research contributes to academic discourse and provides practical guidelines for digital media design and animation.